University Libraries Reaction to Covid-19 Pandemic: The Foremost Central Libraries in Iran - Azam Najafgholinejad; Sedigheh Shakeri (International Journal of Digital Content Management, 2021)
Purpose: The purpose of this study is to explore the university libraries’ responses to the COVID-19 pandemic and determine their services patterns.Method: This study is a qualitative exploration by collecting data through phone and online interviews of selected heads or assistants of thirteen university libraries. The interview recordings were transcribed with the help of callX software. The content of the interviews was analyzed and coded using MaxQDA software and led to the extraction of 220 initial codes.Findings: Almost all the central libraries of the studied universities limited their in-person services during Covid 19 pandemic but engaged with the users and tried to increase digital and remote services. Revamping their web pages, Flexibility in presenting services, development of information dissemination to users were the most important services and activities that central libraries presented in the pandemic era. Two of the most significant services which they have started during this period are librarian booking and online videoconference interviews with the users.Conclusion: although Covid 19 quickly invaded libraries and reduced the opportunity for a quick response, some of the studied central libraries took advantage of the crisis and provided suitable services to students such as setting up digital reference desks, purchase of software to organize electronic resources in the library, online reference interview with users etc.